EDUCATION PROGRAM ON SAFE AND HALAL FOOD PROCESSING FOR STUDENTS, TEACHERS, AND EDUCATIONAL STAFF AT PASUNDAN 1 SENIOR HIGH SCHOOL, CIMAHI CITY - Ikrawan, Yusep Ikrawan; Widiantara, Tantan; Taufik, Yusman; Ghaffar, Rizal Maulana; Ramadhanti, Nadya Arsy; Azarine, Raissa Aurrelia; Sundari, Ayuningtyas Sri; Safari, Daffa Naufal; Hamdani, Fariz Ali; Gibran, Fadlan Mohamad; Asshidiqie, Fakhriza Saukan (Abdi Dosen : Jurnal Pengabdian Pada Masyarakat, 2025)
This community service program was carried out at SMA Pasundan 1 Cimahi and aimed to increase awareness of safe and halal food among students, teachers, and school staff. The activity included educational sessions and practical workshops involving sample testing for food safety. The pre-test average was 50.50%, while post-test scores increased to 86.51%, indicating significant knowledge improvement. This result shows the effectiveness of combining theoretical and practical methods in community education. The program concluded with poster distribution and the development of teaching modules to sustain the impact.